Nidificación del Carpinterito Común (Picummus cirratus) en la provincia de Córdoba - Giraudo, Alejandro R.; Brunello, Duilio; Broggini, Georgina (Nuestras Aves, 1993)
Este artículo no cuenta con un resumen.